Entrepreneurship in Library and Information Science Profession as a Way of Enhancing Economic Empowerment - Olawepo, Saheed Adeshina; Adedeji, Fausat Olufunke (POMLIF Journal of Library and Information Science, 2021)
Societies around the world have always been fueled by the innovations and new products that entrepreneurs bring to the market. This article focused on some business opportunities library and information science professionals can venture into as a way of economy empowerment. It also highlighted the skills necessary for LIS professionals from venturing into entrepreneurship. The paper recommended that LIS professionals develop entrepreneurial culture and mindset and also acquire specific ICT skills in order to exploit the opportunities in the profession, achieve self-employment and remain relevant.